Persepsi Seksualitas Santri Dan Responsi Menghadapi Kekerasan Seksual - Fatni Erlina; Indah Listyorini (Matan : Journal of Islam and Muslim Society, 2025)
Many cases of sexual violence have occurred within Islamic boarding school (pesantren) environments. This study aims to examine the relevance between female students’ perceptions of sexuality and their readiness to protect themselves from the threat of sexual harassment, as well as to explore how sex education is implemented in pesantren settings. This research adopts a quantitative approach, supported by qualitative elements through descriptive statistical analysis. The population consists of female santri in Banyumas Regency, with a sample of 102 respondents selected using non-probability sampling and random homogeneous techniques. The findings indicate that students’ views on aspects of sexuality—such as norms, values, and morality—vary considerably. These differences in interpreting and responding to sexuality are influenced by cultural factors, personal experiences, educational background, and the pesantren environment itself. The results also reveal varying levels of awareness regarding potential risks: some students have received information and training, while others remain less sensitive to the issue. These findings highlight the need for a more structured approach to ensuring the safety and protection of students from potential sexual abuse. The study further identifies the efforts and methods employed by pesantren in providing sex education. While such material is acknowledged to exist, it is not presented systematically as part of a structured curriculum. Ideally, sex education for santri should incorporate instruction on moral values and sexual responsibility, reflecting an effort to integrate religious values with a modern understanding of sexuality